Teaching Global Citizenship: A Teacher Reflects on a Learning-Teaching Event and Implications for Global Citizenship Education - Kornelsen, Lloyd (International Journal for Talent Development and Creativity, 2022)
In narrative style, this paper looks at how a particular teaching-learning event, a meeting in 2003 between Canadian high school students and their Costa Rican host families in Pedrogosso, Costa Rica, unveils pedagogies of global citizenship. By interweaving insights obtained from scholars of education, experiences of students, and reflections by teachers, the author shows how learning for world citizenship often happens in unexpected and unscripted circumstances, when teachers are absent—although, not without responsibility.